High‐Crystalline Regioregular Polymer Semiconductor by Thermal Treatment for Thickness Tolerance Organic Photovoltaics. Issue 9 (27th July 2022) - Yeop, Jiwoo; Park, Kwang Hun; Jeon, Seungju; Kim, Gayoung; Lee, Woojin; Song, Seyeong; Jung, Seo-Hyun; Kim, Yejin; Hwang, Do-Hoon; Lim, Bogyu; Kim, Jin Young
Abstract : To successfully develop a regioregular polymer, poly[4, 8‐bis(5‐(2‐hexyldecyl)thiophen‐2‐yl)benzo[1, 2‐ b :4, 5‐ b ′]dithiophene][5, 5′‐bis(7‐(4‐(2‐butyloctyl)thiophen‐2‐yl)‐6‐fluorobenzo[ c ][1, 2, 5]thiadiazol‐4‐yl)‐2, 2′‐bithiophene] (PDBD‐FBT), a symmetric monomer synthesized in high yield by tin homo‐coupling reactions. PDBD‐FBT is suitable as a donor material in organic photovoltaics (OPVs) because it shows high crystallinity and strong face‐on packing properties. These properties were amplified by thermal annealing (TA). This causes a power conversion efficiency (PCE) enhancement in PDBD‐FBT‐based OPVs. Using PDBD‐FBT as a polymer donor and 2, 2′‐((2 Z, 2′ Z )‐((12, 13‐bis(2‐heptylundecyl)‐3, 9‐diundecyl‐12, 13‐dihydro‐[1, 2, 5]thiadiazolo[3, 4‐ e ]thieno[2″, 3″:4′, 5′]thieno[2′, 3′:4, 5]pyrrolo[3, 2‐ g ]thieno[2′, 3′:4, 5]thieno[3, 2‐ b ]indole‐2, 10‐diyl)bis(methanylylidene))bis(5, 6‐difluoro‐3‐oxo‐2, 3‐dihydro‐1 H ‐indene‐2, 1‐diylidene))dimalononitrile (Y6‐HU) as an electron acceptor, a PCE of 7.91% was achieved without any additive and TA at optimized active layer film thickness of approximately 100 nm. After TA, a PCE of 12.53% was achieved with a 58% increase compared with the reference devices. Owing to the strong crystallinities, trap‐assisted recombination occurs by excessively formed grain boundaries; however, efficient exciton dissociation sufficiently covers these drawbacks. Even in the approximately 340 nm‐thick film condition, this tendency is more pronounced (73% PCE enhancement is observed from 6.17% to 10.69% of PCE in the without and with TA devices, respectively). Our study demonstrates that it is possible to manufacture thickness‐insensitive OPVs based on regioregular polymers with strong crystallinity and face‐on characteristics, thereby providing a solution to the thickness variation of large‐area organic solar cell modules. Abstract : The poly[4, 8‐bis(5‐(2‐hexyldecyl)thiophen‐2‐yl)benzo[1, 2‐ b :4, 5‐ b ′]dithiophene][5, 5′‐bis(7‐(4‐(2‐butyloctyl)thiophen‐2‐yl)‐6‐fluorobenzo[ c ][1, 2, 5]thiadiazol‐4‐yl)‐2, 2′‐bithiophene] (PDBD‐FBT) polymer is used as a donor material for organic photovoltaics by the advantage of increasing crystallinity and improving face‐on packing when the thermal treatment is applied on regioregular polymers. These characteristics are proved by the improved photoconversion efficiency and thickness tolerance of the organic photovoltaics.